L PELATIHAN IMPLEMENTASI KEBIJAKAN KURIKULUM MUATAN LOKAL DI KABUPATEN SUKOHARJO - Leny Noviani; Budiati, Atik Catur; Tuhana; Cahyaningsih, Diana Tantri; Wirajaya, Asep Yudha; Sudarsana; Setyowati, Kristina; Khoiriyah, Siti; Supriyadi; Rinanto, Yudi (Universitas Negeri Surabaya, 2025)
The Sukoharjo Regency Government regrouped 16 elementary schools (SD) into 8 SD in 2022. This regrouping was legalized through Regent's Decree No. 420/376/2022 dated July 12, 2022. One of the reasons for this regrouping was because the number of students was small and not growing. The problem that is a priority for partners is how to overcome misconceptions about the implementation of local wisdom in elementary schools so that it can improve the quality of graduates so that it can increase public interest. The solution to overcome this is the socialization of the concept of local wisdom curriculum, which includes religious content, character education, and local wisdom-based learning. This service method uses a participatory approach. The training activity was attended by 60 people, consisting of school supervisors, principals, and teachers. Participants' understanding of the material can be seen from the participants' ability to compile local content work programs, which are outlined in mind maps during the training activities. Based on feedback from participants, it shows that participants consider this training program very good in terms of: clarity of activity objectives, relevance of activities to participant needs, systematic presentation of materials, added value of the materials presented, time allocation, and achievement of activity objectives.